A revolutionary history of interwar India: violence, image, voice and text - Maclean, Kama (C. Hurst & Co. (Publishers) Ltd, 2015)
Introduction: violence and anticolonialism in India -- The revolutionaries of the Hindustan Socialist Republican Army: histories, actions, activists. Of history and legend: revolutionary actions in North India, 1928-31 ; That hat: infamy, strategy and social communication ; The revolutionary unknown: the secret life of Durga Devi Vohra -- Porous politics: the congress and the revolutionaries, 1928-31. Intermediaries, the revolutionists and the congress ; The revolutionary picture: images and the dynamics of anticolonialism ; 'Gandhi and Balraj': from dominion status to complete independence -- The aftermath: Gandhism and the challenge of revolutionary violence. The Karachi Congress, 1931 ; Controlling political violence: the government, the congress and the HSRA -- Conclusion: the dynamics of anticolonial violence -- Epilogue: Congree and the revolutionaries,1937-1946